64‐4: Manufacturing and Encapsulation Process of Bottom Gate Bottom Contact Thin‐Film Transistors with a Printed Oxide Semiconductor. Issue 1 (30th May 2018) - Kammoun, Nesrine; Krieg, Yvonne; Ngaleu, Guy Williams; Anselmann, Ralf; Renner, Gerhard; Fruehauf, Norbert
Abstract : We present bottom gate bottom contact staggered oxide semiconductor TFTs, manufactured by using an ink‐jet printed metal oxide semi‐conductor material from the company Evonik. The printed TFTs with optimized process and adjusted channel geometry present high charge carrier mobility values between 10 and 15 cm 2 /Vs and on/off current‐ratios of more than 10 6 . The maximum temperature used is 300 °C, which makes the process compatible with the display manufacturing. To achieve a more stable electric behavior and better threshold voltage homogeneity, mainly in the case of positive gate bias stress, we used a solution processed encapsulation to shield the device from the atmospheric effects. The encapsulated TFTs show a considerable stability improvement and present hence an attractive technology alternative for active matrix processes.